Water-energy-food nexus: A case study on medicinal and aromatic plants - Litskas, Vassilis D.; Chrysargyris, Antonios; Stavrinides, Menelaos; Tzortzakis, Nikos G. (My University, 2019)
Medicinal and Aromatic Plants (MAPs) are broadly cultivated in the Mediterranean but their environmental footprint is not very well studied. In this paper, Life Cycle Assessment (LCA) was applied to determine the energy balance, carbon and water footprints (CF and WF, respectively) in 50 farms, organic and conventional, where four MAP species were cultivated; spearmint (Mentha spicata), oregano (Oreganum vulgare), rosemary (Rosmarinus officinalis) and Damask rose (Rosa damascena). The lowest value for energy intensity (EI) was observed for organic spearmint (0.18 MJ/kg fresh weight; f.w.) while the highest for conventional Damask rose (5.80 MJ/kg f.w.). Statistically significant differences were observed in EI between organic and conventional farms for spearmint and Damask rose while no differences were found for oregano and rosemary. The lowest CF was observed for organic rosemary (0.051 kg CO2-eq/kg f.w.) while the highest for conventional Damask rose (0.463 kg CO2-eq/kg f.w.). Statistical differences in the CF between organic and conventional farms for the four species followed the same pattern as for EI. Conventional spearmint had the lowest WF (61.5 L of water/kg f.w.) and organic Damask rose the highest (1522 L of water/kg f.w.). Statistical differences between the two management systems were observed only for Damask rose. The 50 farms were grouped according to the values of three indicators (EI, CF and WF) using cluster analysis. Four clusters were identified with 68% of the farms (34) belonging to the low footprint cluster which contained organic and conventional spearmint, oregano and rosemary farms. The other three clusters contained the (16) Damask rose farms, where the inputs were higher in comparison to the other three species and the highest footprint clusters contained conventional rose farms. Our work suggests that MAPs are viable candidates for the implementation of sustainable agriculture in the Mediterranean.
Keywords: Agriculture; Aromatic plants; Cyprus; Environmental footprints; Organic farming; Sustainability